A Six-Year Review of Ruptured Ectopic Pregnancies at the Olabisi Onabanjo University Teaching Hospital, Sagamu - Shorunmu TO; Lamina MA; Adefuye PO; Oloyede OA; Odusoga OL; Olatunji AO; Sule-Odu AO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Background: Ectopic pregnancy is a major complication of early pregnancy and is a common reason for gynaecological emergency admissions. The ruptured variety accompanied by profuse intra-abdominal haemorrhage is one of the leading causes of maternal mortality in the developing countries. Objective: To describe the local epidemiology of ruptured ectopic pregnancy at the Olabisi Onabanjo University Teaching Hospital (OOUTH), Sagamu. Methods: This was a retrospective study of ruptured ectopic pregnancies managed at OOUTH between January 2009 and December 2014. The case records were retrieved from the medical records department. Other relevant information were obtained from the operating theatre registers and pathology department records for statistical analysis. Results: Sixty-two cases of ruptured ectopic pregnancies were identified out of 2,875 gynaecological admissions and 2,360 deliveries over the specified period. The incidence of ruptured ectopic pregnancies was 1 in 38 deliveries and prevalence of 2.2% of all gynaecological admissions. About 90.7% of the patients studied belonged to the active reproductive age group (21 - 35 years) while 58.0% were of low parity (Para 0 - 1). The leading symptoms included abdominal pain (95.2%) and amenorrhoea (83.9%). The fallopian tubes were the sites of implantation in 96.8% of the cases. There were no cases of heterotopic or cervical pregnancy. All the patients had laparotomy and salpingectomy (partial/total) was the commonest procedure undertaken (79.0%). Anaemia was the most frequent postoperative complication (69.4%), and only one death was recorded (case fatality rate of 1.6%). Conclusion: Ruptured ectopic pregnancy contributed to maternal morbidity and mortality at the study centre. Most of the common predisposing factors in this setting are preventable.